IL-1β primed mesenchymal stromal cells moderate hemorrhagic shock-induced vascular permeability - Nathalie Baudry; Aurélie Campeanu; Clotilde Aussel; Caroline Doutrelon; Marion Grosbot; Sébastien Banzet; Eric Vicaut; Juliette Peltzer (Journal of Translational Medicine)
Abstract Background Hemorrhagic shock (HS) corresponds to absolute hypovolemia creating an imbalance between oxygen supply and consumption. This causes an impaired hemostasis, a systemic inflammatory response, and microvascular permeability which can lead to multiple organ failure (MOF). There is no specific treatment for the endothelial dysfunction that plays a major role in the evolution towards MOF. Mesenchymal stromal cells (MSC) have been used in clinical trials for their immunomodulation and tissue repair capabilities for many years. Moreover, we previously showed that IL-1β-primed-MSC (MSCp) attenuated HS-induced organ injuries. The objective of the study was to determine whether MSCp could prevent the onset of MOF after HS by preventing endothelial dysfunction. Methods We established a rat model of HS, inducing 90 min of HS at a fixed mean arterial pressure of 35 mmHg, followed by resuscitation and transfusion. MSCp treatment was administered intravenously at the onset of resuscitation. After 6 h, we assessed plasma levels of endothelial markers, vascular permeability using Evans Blue (EB) dye, and renal and hepatic water content by measuring the wet-to-dry weight difference. Additionally, we investigated the ability of MSCp to inhibit leukocyte adhesion to activated endothelium in vitro. Results Our results indicate that early administration of MSCp significantly reduced the percentage of water content and EB dye in the liver but not in the kidney. These results were associated with a trend toward decreased plasma levels of Syndecan-1, ICAM-1, vWF, and VCAM-1. In vitro, MSCp reduced leukocyte-endothelial cell adhesion. Together, our results suggest that MSCp help to prevent endothelial dysfunction and vascular leakage, which, in turn, could protect the liver from injury.